L’insularità, l’isolamento e l’autonomia alimentare degli ikoots (Oaxaca, Messico) fra storia, flussi oceanici e catene globali di depauperamento - Cristiano Tallè (Archivio Antropologico Mediterraneo)
The huave/ikoots live on a barrier island between the Pacific Ocean and a vast coastal lagoon system, in the Isthmus of Tehuantepec (Oaxaca, Mexico). In recent decades, their communities have experienced an ever-greater dependence on the supply chains which goes hand in hand with a growing territorial conflict and a progressive loss of fish food autonomy, based on an “ocean-political sovereignty” today in deep crisis. The essay tries to read the double bond between dependence on supply chains and conditions of isolation/insularity, “channeling of vital flows” (water, fish, weather, etc.) and environmental impoverishment, taking into consideration a broad time span (from Cortés' businesses to ongoing mega-projects) and in the light of an ethnographic analysis of the local perception of the interdependence between abundant fishing and the circulation of oceanic flows. From their traditional position as “food processors”, it is above all women today who take charge of the awareness of a well-being shared with the entire aquatic environment, in the face of increasingly intensive (male) fishing and the metabolic crisis of the lagoons, increasingly accentuated.